Architecture of the FindFISH Platform - A Service for Fishermen and More - Lidia Dzierzbicka-Glowacka; Michał Wójcik (TASK Quarterly)
The Knowledge Transfer Platform FindFISH represents a response to the primary issue diagnosed within the fisheries sector, namely the diminishing profitability of fishing endeavors. Additional challenges encompass escalating operational costs borne by fishermen, the necessity for fishermen to embark on longer and more distant voyages in search of fish, the capture of low-value or limited quantities of fish, the tenuous operation at the precipice of profitability due to escalating costs, the imposition of fishing limits and the concomitant difficulties thereof. The construction of the FindFISH Knowledge Transfer Platform through the employment of the Numerical System for Forecasting Marine Environmental Conditions in the Gdańsk Bay for Fisheries is predicated upon in-situ research, environmental data (physicochemical and hydrometeorological), quantitative and qualitative fishing data, as well as numerical modeling of hydrodynamic, physicochemical, and biological parameters within the Gdańsk Bay region. The visualization of data in the form of tables, charts, and maps has been executed and presented via the FindFISH platform, which was established under the auspices of the project.